Language Politeness in The President's Working Visit Speech - Dewi, Atika Puspita; Rahmawati, Laili Etika (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The research aims to explain the principles of language politeness contained in the president's working visit speech. This research uses a qualitative method. The data used in this research is language politeness uploaded on the YouTube channel. The data source used in this research is a video of the president's working visit speech. The location for this research is flexible and can be used as a research location. The research time was carried out from preparation to data analysis over 7 months, namely May – November 2023. This research collected data by applying listening techniques and note-taking techniques. Researchers also use triangulation techniques to verify the validity of the data obtained from the research results. The data analysis method applied is the matching method. The results of research on language politeness in presidential speeches found 15 data containing the principles of language politeness. The use of linguistic unity is the principle of politeness in language which includes the maxim of wisdom, the maxim of generosity, the maxim of respect, the maxim of consensus, the maxim of simplicity, the maxim of consensus and the maxim of sympathy.